Attributing and Managing the Crisis: Lay Representations in Three European Countries. Issue 1 (15th January 2018) - Papastamou, Stamos; Chryssochoou, Xenia; Pavlopoulos, Vassilis; Prodromitis, Gerasimos; Poeschl, Gabrielle; Mari, Silvia; Valentim, Joaquim Pires; Volpato, Chiara; Marchand, Pascal; Ratinaud, Pierre
As part of a larger research project, we asked 1, 806 adults from France, Greece, and Italy (in the larger project, Portuguese students were included) to discuss the causes of the current economic crisis and the strategies that should be adopted by the countries to overcome it. The six factors extracted by the factor analysis revealed that the economic crisis was attributed to the depletion of resources, the weakness of the financial system, planned conspiracy, system inequality, overconsumption, or the weakness of the political system. These causes had cross-national structural equivalence and overconsumption – a people-blaming cause – as opposed to conspiracy attributions to a global power or to structural inequalities inherent to the system. Further analyses found three types of strategies to exit the crisis – conforming to EU requests, rationalizing the public sector, and leaving the European Union – but failed to establish cross-national structural equivalence. Results thus suggest that there is some similarity in the discourses of the media that is reflected on people's perceptions about the causes of the economic crisis, but that the strategies to exit the crisis are more linked to the socioeconomic conditions of the countries.